Aggregated community question answering - Snehasish Banerjee (2015)
The objective of this paper is two-fold objective. First, it introduces ACQUA, a conceptual prototype for an Aggregated Community QUestion Answering site, which provides question clustering and answer prediction functionalities across an aggregation of multiple CQAs. Second, using a combination of questionnaires and group interviews, it conducts an evaluation of users’ behavioral intention to adopt ACQUA based on four parameters, namely, perceived usefulness, perceived ease of use, competence, and usability. Results indicate that the behavioral intention to adopt ACQUA was generally promising. In particular, ACQUA received favorable responses from most participants in terms of perceived usefulness, perceived ease of use, and competence. In terms of usability however, the consensus was not completely in favor of ACQUA. Three implications arising from the findings are discussed. Finally, the paper concludes with notes on limitations and future work.